A Qualitative Analysis of State Level Tests of National Talent Search Examination - Chandrasekhar, K.; Agrawal, Mamta (JOURNAL OF INDIAN EDUCATION, 2010)
National Talent Search Examination scholarship is a most coveted scholarship scheme in the country. It operated at class VIII level and 1000 talented students selected through the National Talent Search Examination are awarded the scholarship till their end of the studies. Since the selection procedure follows a two stage procedure in which the first stage is conducted by states, it was felt necessary to assess the quality of their tests. Because from some states, very few or no candidate figure in the final selection. This paper presents the analysis of state level National Talent Search tests used for nominating students for the national level examination.